2013
DOI: 10.5897/jen2013.0075
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity and total phenolic content of earthworm paste of Lumbricus rubellus (red worm) and Eudrilus eugenia (African night crawler)

Abstract: Earthworm paste (EP) has many therapeutic properties such as antioxidant, anti-inflammatory, anticancer and antibacterial activities. Antioxidant properties of the earthworm paste extract may attribute to high phenolic compounds. This study involved quantification of phenolic compounds and evaluation of the antioxidant activity of earthworm paste (EP) from Lumbricus rubellus (red worm) and Eudrilus eugeniae (African night crawler). Three types of solvents were used: 75% methanol, 80% methanol and 80% ethanol. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…We believe the addition of antiproteases may have prevented enzyme degradation and hence contributed to higher enzyme activities even when expressed as a fraction of the protein concentration. This is an important finding and may explain the differences in antioxidant enzyme activities and LPO between the present study and those reported by others (Pan et al 2010; Aldarraji et al 2013; Muthu and Durairaj 2015).…”
Section: Discussionsupporting
confidence: 68%
“…We believe the addition of antiproteases may have prevented enzyme degradation and hence contributed to higher enzyme activities even when expressed as a fraction of the protein concentration. This is an important finding and may explain the differences in antioxidant enzyme activities and LPO between the present study and those reported by others (Pan et al 2010; Aldarraji et al 2013; Muthu and Durairaj 2015).…”
Section: Discussionsupporting
confidence: 68%
“…Calculation of phenolic content is done by applying the formula: Ethanol as solvent extracted phenolic content from the coelomic fluid of the Eisenia fetida was significant. The highest concentration (Aldarraji et al, 2013) was taken for coelomic fluid total phenolic content and findings from the yields justify the work done by many scientists (Pinelo et al, 2004;Spigno et al, 2007;Turkmen et al, 2007). Solubility of phenolic compounds were found higher in ethanol.…”
Section: Quantification Of Phenolic Compounds Contentssupporting
confidence: 57%
“…In general, the average content of phenols found for yacon in this study was elevated (4.2 ± 1.48 mg GAE per g of yacon), higher than those found by Valentová and Ulrichová (2003) and Lachman et al (2004) who obtained approximately 2 mg g −1 fresh cut yacon, but it is worth to mention that the classical methodology applied to assess the phenol concentrations can lead to overestimated results. Folin-Ciocalteu spectrophotometric method is the most commonly used; however, it is not specific, because the reaction on which this method is based on involves all of the phenolic groups in the media, as well as other reducer substances added or naturally present in food, such as ascorbic acid, sugars, and a few amino acids (Naczk and Shahidi 2004;Ronald et al 2005;Zhao et al 2006;Aldarraji et al 2013).…”
Section: Total Phenolic Compounds In Minimally Processed Yaconmentioning
confidence: 98%